Assessment of Periodontal Ligament Fibroblast Viability in Dymatize® Elite Casein as a Transport Medium for Avulsed Teeth at Different Time Intervals (An in - vitro study) (Mustansiria Dental Journal, 2023)
AbstractAim: To evaluate the effectiveness of a sports dietary supplement, which is Dymatize® Elite Casein (micellar casein), as a storage medium for avulsed teeth compared to Hank’s balanced salt solution at three-time intervals.Methods: One hundred teeth freshly extracted for orthodontic treatment. Were divided into Hank’s balanced salt solution, Dymatize® Elite Casein, a Dry group, and a control that tested directly after extraction. Experimental groups' teeth were immediately immersed in the media and subdivided into three groups at time intervals (1 hr, 4 hrs, and 8 hrs). Cells of PDL were examined after being scraped, and labeled with trypan blue using a light microscope and a hemocytometer. The data were statistically analyzed, using one-way ANOVA with Graph Pad Prism 7. And, Post Hoc Tukey's test performed inferential to compare each test group to all other groups.Results: All groups showed highly significant changes, except for Dymatize® and control at one hour, which showed non-significant differences. All experimental groups had highly significant differences after 4 and 8 hours.Conclusion: The Dymatize® Elite Casein could serve effectively as a transport medium and preserve fibroblast viability over time ensuring replantation success. It is a good substitute with its superior properties.